Long-term follow-up of a vaccination program for infants born to HBsAg-positive mothers in Stockholm County, Sweden. Issue 4 (22nd January 2020) - Insulander, Mona; Lindh, Gudrun; Stenkvist, Jenny; Samuelson, Agneta; Fischler, Björn
Abstract: We investigated the long-term antibody response to hepatitis B virus (HBV) vaccination in babies born to chronically infected mothers. They received one dose of monovalent HBV vaccination at birth and one month of age, followed by 3 doses of hexavalent vaccine including an HBV component at ages 3, 5, and 12 months, respectively, with a very high percentage of protective anti-HBs levels at 13 months. At the age of 8–12 years, 56 out of 68 children (82%) had protective levels of anti-HBs, two had signs of anti-HBc seroconversion without any history of clinical disease and none had ongoing infection. A small subgroup was retested after one booster dose, in all resulting in increase in anti-HBs from below 10 IU/L to levels corresponding to protective immunity. We conclude that this vaccination strategy is effective throughout the first decade of life in avoiding chronic infection and in maintaining a good serological response.